Optimistic Postpandemic Outlooks for International Branch Campuses - Kleibert, Jana (International Higher Education, 2022)
International higher education has been severely impacted by the COVID-19 pandemic. This article reveals how international branch campuses across the globe have been impacted by the pandemic and how institutional strategies have been adapted. The results show how international branch campuses, while being heavily affected, simultaneously offer opportunities for geographically diversified teaching that may increase the resilience of the home campus. Campus managers express high levels of optimism about the future of international branch campuses.